Perlindungan Hukum Produk Lokal Tembe Nggoli Bima sebagai Upaya Peningkatan Ekonomi dalam Perspektif Sustainable Development Goals - Fitrah; Taufik Firmanto; Nasrullah (CV Rewang Rencang, 2025)
This study examines the legal protection of Tembe Nggoli, a traditional product from Bima, in the context of achieving the Sustainable Development Goals (SDGs). Using a mix-methods approach, the research found weak protection in both regulatory and practical aspects. The absence of specific local regulations, low legal literacy, and minimal institutional support are key challenges. Yet, local products have strong potential to improve welfare, preserve culture, and enhance economic competitiveness. Therefore, systematic and sustainable legal protection is essential to support the development of a local economy rooted in cultural wisdom.